Military integration after civil wars : multiethnic armies, identity and post-conflict reconstruction - Gaub, Florence ([S.l.] : Routledge, 2010)
This book examines the role of multiethnic armies in post-conflict reconstruction, and demonstrates how they can promote peacebuilding efforts. The author challenges the assumption that multiethnic composition leads to weakness of the military, and shows how a multiethnic army is frequently the impetus for peacemaking in multiethnic societies. Three case studies (Nigeria, Lebanon and Bosnia-Herzegovina) determine that rather than external factors, it is the internal structures that make or break the military institution in a socially challenging environment. The book finds that where the political will is present, the multiethnic military can become a symbol of reconciliation and coexistence. Furthermore, it shows that the military as a professional identity can supersede ethnic considerations and thus facilitates cooperation within the armed forces despite a hostile post-conflict setting. In this, the book challenges widespread theories about ethnic identities and puts professional identities on an equal footing with them. The book will be of great interest to students of military studies, ethnic conflict, conflict studies and peacebuilding, and IR in general Florence Gaub is a Researcher and Lecturer at the NATO Defence College in Rome. She holds a PhD in International Politics from Humboldt University, Berlin.
Keywords: Armed Forces--Minorities; Ethnic conflict--Prevention; Multinational states; Postwar reconstruction